2014
DOI: 10.3892/ol.2014.2014
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol inhibits the phosphatidylinositide 3-kinase/protein kinase B/mammalian target of rapamycin signaling pathway in the human chronic myeloid leukemia K562 cell line

Abstract: Resveratrol inhibits the initiation, promotion and progression of tumors, however, the mechanism by which resveratrol inhibits the proliferation of the human chronic myeloid leukemia K562 cell line remains unclear. The present study was conducted to investigate the effect of resveratrol on the activation of the phosphatidylinositide 3-kinase (PI3K)/protein kinase B (Akt)/mammalian target of rapamycin (mTOR) signaling cascade in K562 cells. Resveratrol showed significant cytotoxic effects and induced apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 42 publications
(34 reference statements)
0
19
0
1
Order By: Relevance
“…In addition, Res was also reported to inhibit colon cancer cell proliferation through inhibition of PI3K and Wnt/β-catenin signaling pathways (12). Sui et al (13) showed that Res exhibited significant cytotoxic effects and induced apoptosis in K562 chronic myeloid leukemia cells via inhibiting the PI3K signaling pathway. The present study also found that Res had an inhibitory effect on the activity of the PI3K signaling pathway in chondrosarcoma cells, suggesting that inhibition of PI3K signaling may be a common molecular mechanism by which Res suppresses cancer cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Res was also reported to inhibit colon cancer cell proliferation through inhibition of PI3K and Wnt/β-catenin signaling pathways (12). Sui et al (13) showed that Res exhibited significant cytotoxic effects and induced apoptosis in K562 chronic myeloid leukemia cells via inhibiting the PI3K signaling pathway. The present study also found that Res had an inhibitory effect on the activity of the PI3K signaling pathway in chondrosarcoma cells, suggesting that inhibition of PI3K signaling may be a common molecular mechanism by which Res suppresses cancer cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Res has been demonstrated to suppress proliferation but induce apoptosis in multiple types of cancer (7,13). However, the effects of Res on chondrosarcoma cell proliferation and apoptosis remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for the involvement of the PI3K pathway in the activation observed in the α‐MEM + is the presence of insulin in the medium, which acts primarily by activating this pathway (Khorami, Movahedi, Huzwah, & Sokhini, ). In regard to resveratrol, it exerts an anticancer effect by causing apoptosis in a range of cell lines through different mechanisms, including downregulation of the PI3K/AKT pathway (Chen et al, ; Sui et al, ). Interestingly, follicular activation observed in 2 µM resveratrol after PI3K inhibition was similar to that found in the control medium (α‐MEM + ) without using the inhibitor LY294002.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol is known to have differential effects based on physiological, pathological and pharmacological conditions in various biological systems (Banu, Stanley, Sivakumar, Arosh, & Burghardt, 2016). In cancer cells, resveratrol induced apoptotic cell death, and therefore is used as a chemotherapeutic agent through downregulation of the PI3K/AKT pathway (Chen, Ganapathy, Singh, Shankar, & Srivastava, 2010;Sui, Ma, Bai, Li, & Xu, 2014). In contrast, resveratrol also has beneficial effects in other cells such as oocytes and granulosa cells.…”
Section: Introductionmentioning
confidence: 99%
“…The PI3K/Akt pathway is involved in the regulation of a number of cellular processes including cell death and survival, cell proliferation, protein synthesis and cell metabolism (23,24). Accumulating evidence has indicated that activation of the PI3K/Akt pathway may confer acquired resistance to chemotherapeutic drugs with different mechanisms of actions: ADR, mitoxantrone, 5-fluorourocil, etoposide, camptothecin, etc (20,21).…”
Section: Discussionmentioning
confidence: 99%